Radioresistant Nasopharyngeal Carcinoma Cells Exhibited Decreased Cisplatin Sensitivity by Inducing SLC1A6 Expression - Hao, Wenwen; Wu, Lisha; Cao, Linhui; Yu, Jinxiu; Ning, Li; Wang, Jingshu; Lin, Xiaoping; Chen, Yanfeng (Frontiers in Pharmacology, 2021)
Cisplatin-based regimens are commonly used for the treatment of nasopharyngeal carcinoma (NPC) in patients who receive concurrent chemoradiotherapy. The sensitivity of NPC cells to cisplatin is closely associated with the efficacy of radiation therapy. In this study, we established two radioresistant NPC cell lines, HONE1-IR and CNE2-IR, and found that both cell lines showed reduced sensitivity to cisplatin. RNA-sequence analysis showed that SLC1A6 was upregulated in both HONE1-IR and CNE2-IR cell lines. Downregulation of SLC1A6 enhanced cisplatin sensitivity in these two radioresistant NPC cell lines. It was also found that the expression of SLC1A6 was induced during radiation treatment and correlated with poor prognosis of NPC patients. Notably, we observed that upregulation of SLC1A6 led to elevating level of glutamate and the expression of drug-resistant genes, resulted in reduced cisplatin sensitivity. Our findings provide a rationale for developing a novel therapeutic target for NPC patients with cisplatin resistance.